Photoinduced oxidation of triphenylphosphine isolated in a low-temperature oxygen matrix - Reva, Igor (2008)
http://www.sciencedirect.com/science/article/B6TFN-4TXF81D-3/2/a7ee21821936ceab2970c58d4ce846aa